Effect of the Phenyl Substituent on Two-proton-coupled Electron Transfer between Hydroquinone and Superoxide Radical Anion - Tatsushi NAKAYAMA (Electrochemistry)
Proton-coupled electron transfer (PCET) plays a critical role in processes ranging from biological energy conversion to catalysis and materials science. In this study, the effect of a phenyl substituent on hydroquinone reactivity is examined through the PCET reaction between 2-phenylbenzene-1,4-diol (Ph-H2Q) and electrogenerated superoxide radical anion (O2•−) in N,N-dimethylformamide. Using cyclic voltammetry (CV) and in situ electrolytic electron spin resonance (ESR) spectroscopy, it was demonstrated that Ph-H2Q undergoes a concerted two-proton-coupled electron transfer (2PCET) process. The CV profiles show that in the presence of Ph-H2Q the usual reversible dioxygen/O2•− redox couple becomes irreversible, indicating that the initial proton transfer (PT) from Ph-H2Q to O2•− is followed by an electron transfer and a subsequent PT to yield the quinone radical anion (Ph-Q•−). The ESR spectra confirmed the formation of Ph-Q•− via characteristic hyperfine splitting, with no significant spin delocalization onto the phenyl ring. Density functional theory calculations revealed that the frontier orbital energy variations along the 2PCET pathway for Ph-H2Q closely resemble those of unsubstituted hydroquinone, indicating minimal inductive or resonance effects from the phenyl group. Although the phenyl substituent is electronically similar to hydrogen in terms of PCET mechanism, its larger steric bulk slightly diminishes reactivity at higher concentrations. The thermodynamic analysis further confirmed that the overall 2PCET process is exergonic. These findings elucidate the subtle role of the phenyl substituent in PCET reactions, with implications for the rational design of hydroquinone-based redox systems.